The Relationship Between Race and Obesity Among Non-Hispanic White and Non-Hispanic Black Men by Education Level - Corina Mills; Hossein Zare; Genie Han; Courtney Thomas Tobin; Roland J. Thorpe (American Journal of Men's Health)
Prior disparities in obesity research emphasize socioeconomic status as a potential driver of White-Black differences in obesity prevalence, but there is a paucity of research examining the influence of education on the observed racial difference among men. The objective of this study was to determine whether the relationship between race and obesity varies by education level among Non-Hispanic White (NHW) and Non-Hispanic Black (NHB) men. We used 1999 to 2016 National Health and Nutrition Examination Survey data consisting of a sample of 13,583 men (9,459 NHW and 4,124 NHB). Race and Ethnicity were determined by self-reports of whether they were Hispanic or not and their racial group. Education was based on self-reporting of the highest grade level or level of school completed and categorized as: less than high school, high school diploma or General Equivalency Diploma, some college or associate degree, and college degree or above. Thirty-four percent of the men were obese (body mass index [BMI] > 30 kg/m 2 ); a higher proportion of NHB men reported being obese than NHW men (36.0%, n  = 1,508, vs. 33.8%, n  = 3,140; p  = .049). Adjusting for age, marital status, income, insurance status, smoking status, drinking status, self-rated health, physical inactivity, and the number of chronic conditions, NHB men with a college degree or above had a higher prevalence of obesity (prevalence ratio: 1.21, confidence interval [1.06, 1.39]) than NHW men. Findings suggest that among college-educated NHW and NHB men, there is a relationship between race/ethnicity and obesity prevalence.